Correlation and path coefficient analyses of qualitative and quantitative traits in selected bottle gourd landraces. (2nd October 2016) - Mashilo, Jacob; Shimelis, Hussein; Odindo, Alfred
ABSTRACT: Knowledge on associations between yield and related traits is vital to improve selection efficiency in cultivar improvement. This study determined the relationships among qualitative and quantitative traits in bottle gourd landraces using simple correlation and path analyses. Results showed significant and positive correlations between the number of fruits per plant (NFPP) with number of male flowers (NMF), number of female flowers (NFF), plant height (PHT) and number of branches (NB). Number of seeds per fruit (NSPF) positively correlated with PHT, NMF, NFF, NB and fruit weight (FW). Fruit texture, degree of warts (DW), fruit shape (FS), and degree of neck bending, stem-end fruit shape and fruit neck length (FNL) had significant negative correlations with NFPP or NSPF. Path analysis revealed high direct path coefficient value (0.96) between FW and NSPF. Also, positive direct path coefficient value (0.92) was exhibited between NFF and NFPP. Relatively high direct path coefficient value (0.47) was exhibited between DW and NSPF. This study demonstrated that selection for increased FW and NFF may improve genetic gain in seed yield and fruit yield in bottle gourd breeding. Using the above analyses, the following landraces such as BG-06, BG-07, BG-09, BG-11, BG-13, BG-24 and BG-67 were selected for breeding.